2011
DOI: 10.1002/acr.20564
|View full text |Cite
|
Sign up to set email alerts
|

Unité Rhumatologique des Affections de la Main (URAM) scale: Development and validation of a tool to assess Dupuytren's disease–specific disability

Abstract: Objective. To our knowledge, no functional outcome measure has been developed and validated for Dupuytren's disease. We aimed to develop and validate a patient-reported functional outcome measure for Dupuytren's disease. Methods. Patients with Dupuytren's disease (n ‫؍‬ 9) and medical experts (n ‫؍‬ 7) provided input and opinions about limiting activities that were difficult to perform because of Dupuytren's disease for item generation. The provisional scale was studied in an independent sample of patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 35 publications
3
91
1
4
Order By: Relevance
“…Scores specific to DD such as the Unité Rhumatologique des Affections de la Main Scale and the Southampton Dupuytren Scoring Scheme (SDSS) have been devised but have not been fully validated. 5,10 Patient satisfaction is therefore a fundamental outcome measure that encompasses many aspects of treatment. Witthaut et al 4 reported that 71% of 587 patients treated with CCH were "very satisfied" and 21% "quite satisfied" 9 months after treatment.…”
mentioning
confidence: 99%
“…Scores specific to DD such as the Unité Rhumatologique des Affections de la Main Scale and the Southampton Dupuytren Scoring Scheme (SDSS) have been devised but have not been fully validated. 5,10 Patient satisfaction is therefore a fundamental outcome measure that encompasses many aspects of treatment. Witthaut et al 4 reported that 71% of 587 patients treated with CCH were "very satisfied" and 21% "quite satisfied" 9 months after treatment.…”
mentioning
confidence: 99%
“…We read with great interest the recent article in Arthritis Care & Research by Beaudreuil and coworkers regarding the validation of a Dupuytren's disease-specific short questionnaire to assess patient-reported functional outcome (1). We fully agree with the authors that measures to assess patient-reported outcome are paramount, especially in a disease like Dupuytren's contracture.…”
mentioning
confidence: 71%
“…[36][37][38][39][40] Beaudreuil et al addressed this issue by developing the Unité Rhumatologique des Affections de la Main scale, a validated Dupuytren-specific subjective assessment scheme, 41 shown in Table 1. The scale was a final reduction of a list of 52 initial functional questions to the minimum set that statistically correlated best with the Tubiana range-of-motion score and a visual analogue disability score.…”
Section: Dupuytren-specific Assessmentmentioning
confidence: 99%